The effects of natural nano-sized clinoptilolite and Nigella sativa supplementation on serum bone markers in diabetic rats - Yalda Salari Lak; Sirous Khorram; Mehran Mesgari Abbasi; Mohammad Asghari-Jafarabadi; Ali Tarighat-Esfanjani; Elahe Bazri; Hossein Omidi (BioImpacts, 2019)
Introduction: Many studies confirm that diabetes mellitus is associated with higher risks of bone fracture. The beneficial effects of Nigella sativa (NS) and clinoptilolite in preventing/reducing some diabetes-related disorders have been shown. This study was conducted to examine the effects of separate and concurrent supplementation of natural nano-sized clinoptilolite (NCLN) and NS on serum bone markers in rats with type 2 diabetes. Methods: A total of 42 (case=36 and control=6) adult male Wistar rats were divided into 2 groups: diabetic and non-diabetic. An oral glucose tolerance test and a homeostatic model assessment of insulin resistance (HOMA-IR) test were conducted to confirm diabetes. Then, the diabetic group was divided into 4 subgroups: [1] control (n=9), [2] NS 1%/food (n=9), [3] NCLN 2%/food (n=9), [4] NS 1%/food + NCLN 2%/food (n=9). After 7 weeks, serum levels of bone markers were determined using ELISA kits. Results: Analysis showed that serum levels of alkaline phosphatase (ALP) in the NCLN group (1318.6 ± 217.5 U/L) was significantly (P<0.05) higher than other intervented groups. On the other hand, serum levels of calcium in NCLN+NS group (10.8 ± 2.6 mg/dL) were higher (P=0.027) compared to all other study groups. However, rats in the NS group had higher (535.8 ± 49.3 pg/mL) PTH (P<0.0001) compared to other supplementation groups. There were no significant differences in vitamin D and osteoprotegerin. Conclusion: The results of the current study suggest that bone mineralization may be affected by concurrent use of NS and NCLN through influencing calcium circulation. Moreover, dietary NS administration is strongly related to an augmented level of PTH.